2021
DOI: 10.1016/j.ultsonch.2021.105632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solid particles on cavitation behaviors and laser-induced degradation in aqueous suspension

Abstract: Highlights Research on a novel degradation method with laser technology. Dynamics of laser-induced cavitation bubbles in suspension has been studied. Relationship exists between bubble size and degradation extent. Particles have both positive and negative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Treatment) is about five times less, with 81 articles. This indicates a quite specific focus on ultrasonic cavitation and hydrodynamic cavitation with respect to other cavitation-induced processes, but the recent J o u r n a l P r e -p r o o f discoveries on optical cavitation and particle cavitation application and optimization will make studies on this topic more common in the future (Geng et al, 2021;Luo et al, 2021). The results also showed that the journals traditionally focused on environmental chemistry (i.e., Chemosphere, J. of Hazardous Materials, J.…”
Section: Journal Analysismentioning
confidence: 99%
“…Treatment) is about five times less, with 81 articles. This indicates a quite specific focus on ultrasonic cavitation and hydrodynamic cavitation with respect to other cavitation-induced processes, but the recent J o u r n a l P r e -p r o o f discoveries on optical cavitation and particle cavitation application and optimization will make studies on this topic more common in the future (Geng et al, 2021;Luo et al, 2021). The results also showed that the journals traditionally focused on environmental chemistry (i.e., Chemosphere, J. of Hazardous Materials, J.…”
Section: Journal Analysismentioning
confidence: 99%
“…Cavitation is a common phenomenon in water jets, where cavitation bubbles collide with the material surface and collapse near the surface boundary, causing erosion damage to the target surface [2]. Cavitation impacts, including micro jets and shock waves generated by the collapse of cavitation bubbles, are one of the main mechanisms leading to cavitation erosion [3]. The distance between the cavitation nozzle and the target surface has a significant impact on cavitation erosion, resulting in various morphological changes on the material surface.…”
Section: Introductionmentioning
confidence: 99%